2016
DOI: 10.1016/j.immuni.2016.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Innate Lymphoid Cells Are Depleted Irreversibly during Acute HIV-1 Infection in the Absence of Viral Suppression

Abstract: Innate lymphoid cells (ILCs) play a central role in the response to infection by secreting cytokines crucial for immune regulation, tissue homeostasis, and repair. Although dysregulation of these systems is central to pathology, the impact of HIV-1 on ILCs remains unknown. We found that human blood ILCs were severely depleted during acute viremic HIV-1 infection and that ILC numbers did not recover after resolution of peak viremia. ILC numbers were preserved by antiretroviral therapy (ART), but only if initiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
163
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 131 publications
(197 citation statements)
references
References 44 publications
(68 reference statements)
20
163
2
Order By: Relevance
“…Surprisingly, ILC3 can maintain their phenotype and function even in the absence of ROR γ t expression and persist for a significant length of time 53. Nonetheless, changes in dietary metabolites, chronic inflammation or infectious insult result in disruption of ILC3 effector functions or even irreversible depletion of ILC from the intestinal tissue altogether 54, 55. Further studies are required to understand how ILC3 numbers and functions are maintained and how they can be restored following damage or infection‐induced perturbation.…”
Section: Tissue‐resident Ilc3: From Cradle To Gravementioning
confidence: 99%
“…Surprisingly, ILC3 can maintain their phenotype and function even in the absence of ROR γ t expression and persist for a significant length of time 53. Nonetheless, changes in dietary metabolites, chronic inflammation or infectious insult result in disruption of ILC3 effector functions or even irreversible depletion of ILC from the intestinal tissue altogether 54, 55. Further studies are required to understand how ILC3 numbers and functions are maintained and how they can be restored following damage or infection‐induced perturbation.…”
Section: Tissue‐resident Ilc3: From Cradle To Gravementioning
confidence: 99%
“…HIV-1 infection in humans in particular is associated with impaired gut barrier and translocation of commensal bacteria which drive systemic inflammation [134]. While profound depletion of infected CD4 + T cells is the hallmark of HIV-1 infection, recent studies have demonstrated dysregulation of ILC3 in the blood, lymph, and/or intestinal tissues of HIV-1-infected humans or humanized mice and SIV-infected macaques [130133]. Thus, in the setting of HIV or SIV infection, loss of tissue-protective ILC3 responses may lead to loss of mucosal tolerance towards gut commensals, propagating intestinal and systemic inflammation.…”
Section: Loss Of Tolerance: Dysregulated Ilc3 Responses In Human Diseasementioning
confidence: 99%
“…Thus, in the setting of HIV or SIV infection, loss of tissue-protective ILC3 responses may lead to loss of mucosal tolerance towards gut commensals, propagating intestinal and systemic inflammation. In support of this, loss of circulating ILC frequencies coincides with the elevation of markers associated with gut barrier breakdown and bacterial translocation [130, 135]. In addition, SIV-infected macaques have reduced frequencies of small intestinal IL-17-producing ILCs following initial and persisting infection [132].…”
Section: Loss Of Tolerance: Dysregulated Ilc3 Responses In Human Diseasementioning
confidence: 99%
See 2 more Smart Citations